Precipitation and Neutralization of Heparin from Different Sources by Protamine Sulfate - John Hogwood; Barbara Mulloy; Elaine Gray (MDPI AG, 2017)
Current therapeutic unfractionated heparin available in Europe and US is of porcine mucosal origin. There is now interest, specifically in the US, to use bovine mucosa as an additional source for the production of heparin. The anticoagulant action of heparin can be neutralized by protamine sulfate, and in this study the ability of protamine to bind and neutralize the anticoagulant activities of heparin from porcine mucosa, bovine mucosa and bovine lung were assessed. Protamine sulfate was able to bind and precipitate similar amounts of heparins from different sources on a mass basis. However, differential amounts of anticoagulant activities were neutralized by protamine sulfate, with neutralization of porcine mucosa more effective than for bovine lung and bovine mucosa. For all heparins, potentiation of thrombin inhibition by antithrombin and heparin cofactor II was preferentially neutralized over antithrombin-mediated inhibition of factor Xa or plasma clotting time. Whole blood thromboelastography showed that neutralization by protamine sulfate was more effective than the antithrombin dependent thrombin inhibition assays indicated. While there was no absolute correlation between average or peak molecular weight of heparin samples and neutralization of anticoagulant activity, correlation was observed between proportions of material with high affinity to antithrombin, specific activities and neutralization of activity.